162 Collegiate coaches' beliefs about concussion safety, culture of concussion on campus, and their role in concussion management. (11th May 2020) - Kneavel, Meredith; Darmiento, Alexandra; Madden, Meredith; Crossan, Jordyn
Abstract : Statement of Purpose: The purpose of this study was to explore the beliefs of NCAA coaches across Divisions I, II, & III about their role in concussion management, perspectives about the culture of concussion on their campuses, and their thoughts on concussion safety. Methods/Approach: As part of a larger survey, open-ended questions were included to explore coaches' attitudes and perceptions of their role in concussion management, the culture of concussion on their team and campus, reporting behaviors of athletes, and overall thoughts on concussion. Colleges from all three divisions of the NCAA were randomly selected based on the proportions represented (31% DI, 27% DII, 41% DIII). Coach and assistant coach emails from selected colleges of contact/collision or limited contact sports were sent a link to the survey. Qualitative data was analyzed using a phenomenological, inductive approach. Results: Thematic analysis suggests that coaches believe their role was one of supporting the Athletic Trainers and healthcare professionals as well as coaching to instruct and enforce safety. They also indicated that concussion are serious although some indicated concussions are overly-hyped. Coaches indicated that reporting behavior is mixed with some suggesting that athletes report and others indicating that athletes do not report or underreport. Coaches provided reasons they thought athletes may under or over report as well. They also indicated that concussions are serious but better diagnostic assessments are needed and return to play protocols are too long. Conclusion: Overall, our findings suggest that coaches report cautious attitudes towards concussion, but there are areas for improvement. Significance and Contributions to Injury and Violence Prevention Science: Exploring the culture of concussion from the perspective of coaches contributes to the socio-ecological framework to more fully understand the larger context in which student-athletes are reporting concussions and provides an understanding of how to target future education.